A class of multilinear bounded oscillation operators on measure spaces and applications. - Cao, Mingming; Ibañez-Firnkorn, Gonzalo; Rivera Ríos, Israel P.; Xue, Qingying; Yabuta, Kôzô (Springer Nature, 2023)
recent years, dyadic analysis has attracted a lot of attention due to the conjecture. It has been well understood that in the Euclidean setting, Calderón–Zygmund operators can be pointwise controlled by a finite number of dyadic operators with a very simple structure, which leads to some significant weak and strong type inequalities. Similar results hold for Hardy–Littlewood maximal operators and Littlewood–Paley square operators. These owe to good dyadic structure of Euclidean spaces. Therefore, it is natural to wonder whether we could work in general measure spaces and find a universal framework to include these operators. In this paper, we develop a comprehensive weighted theory for a class of Banach-valued multilinear bounded oscillation operators on measure spaces, which merges multilinear Calderón–Zygmund operators with a quantity of operators beyond the multilinear Calderón–Zygmund theory. We prove that such multilinear operators and corresponding commutators are locally pointwise dominated by two sparse dyadic operators, respectively. We also establish three kinds of typical estimates: local exponential decay estimates, mixed weak type estimates, and sharp weighted norm inequalities. Beyond that, based on Rubio de Francia extrapolation for abstract multilinear compact operators, we obtain weighted compactness for commutators of specific multilinear operators on spaces of homogeneous type. A compact extrapolation allows us to get weighted estimates in the full range of exponents, while weighted interpolation for multilinear compact operators is
Política de acceso abierto tomada: https://openpolicyfinder.jisc.ac.uk/id/publication/8105
Keywords: Desigualdades (Matemáticas); Calderón-Zygmund, Operadores de; Bounded oscillation operators; Rubio de Francia extrapolation; Measure spaces; Sharp weighted norm inequalities; Weighted compactness